PENGEMBANGAN PERANGKAT PEMBELAJARAN IPA BERBASIS MODEL PEMAKNAAN UNTUK MELATIHKAN KETERAMPILAN PROSES SAINS DAN MENANAMKAN KARAKTER - Suwar, Suwar; Wasis, Wasis; Koestiari, Toeti (Universitas Negeri Surabaya, 2014)
The research was aimed to produce a science physics learning package based on the Model Pemaknaan to facilitate science process skills and cultivate character on the subject of Electromagnetic Induction. The object is achieved through the process of describing the feasibility, practicality, and effectiveness of learning package are developed. This type of research is the development of research, to develop a learning package including syllabus, lesson plans, worksheets, student textbooks, and learning outcomes assessment sheet. The researcher developed the learning package using 4-D and used One Group Pre Test ? Post Test Design during the implementation. The subjects in this research is learning package, were tested on students of SMP Negeri 2 Mojokerto. Data collection was conducted in three sessions. Analysis of experimental data showed that the developed learning package categorized feasible, practical, and effective. Feasibility in terms of legibility student textbooks was 90%, and validation results were expressed valid. Demonstrated the practicality of enforceability lesson plan average of 97.6%, 76.7% student's activity. The effectiveness of the learning package is shown with 82.4% cognitive learning outcomes, 94.6% psychomotor, 97.3% science process skills, and 95.8% affective average (100% moral knowing, 100% moral feeling, 87.5% acting morally), and 92.1% the positive response of students (100 % respond positively to the interpretation phase, characteristic of Model Pemaknaan. Based on the results of data analysis concluded that the science physics learning package based Model Pemaknaan in the subject matter of electromagnetic induction feasible, practical, and effective to use in learning tofacilitate science process skills and cultivate character of junior high school students. Tujuan penelitian ini adalah menghasilkan perangkat pembelajaran IPA Fisika berbasis model pemaknaan untuk melatihkan keterampilan proses sains dan menanamkan karakter pada pokok bahasan Induksi Elektromagnetik. Tujuan tersebut dicapai melalui proses mendiskripsikan kelayakan, kepraktisan, dan keefektifan perangkat pembelajaran yang dikembangkan. Jenis penelitian ini adalah penelitian pengembangan, yaitu mengembangkan perangkat pembelajaran meliputi Silabus, RPP, LKS, BAS, dan LPHB. Model pengembangan perangkat yang digunakan adalah model pengembangan 4-D, sedangkan dalam uji coba perangkat digunakan rancangan One Group Pretest ? Posttest Design. Subjek dalam penelitian ini adalah perangkat pembelajaran yang diujicobakan pada siswa SMP Negeri 2 Mojokerto. Pengambilan data dilakukan dalam tiga kali pertemuan. Analisis data penelitian menunjukkan bahwa perangkat pembelajaran yang dikembangkan berkategori layak, praktis, dan efektif. Kelayakan ditinjau dari keterbacaan BAS 90% dan hasil validitasi yang menyatakan perangkat pembelajaran valid. Kepraktisan ditunjukkan dari keterlaksanaan RPP rata-rata 97,6%, aktivitas siswa 76,7%. Keefektifan perangkat pembelajaran ditunjukkan dengan hasil belajar kognitif 82,4%, psikomotor 94,6%, keterampilan proses sains 97,3%, dan afektif rata-rata 95,8% (moral knowing 100%, moral feeling 100%, moral acting 87,5%), serta respon positif siswa 92,1 % (100% merespon positif terhadap fase pemaknaan, ciri khas model pemaknaan). Berdasarkan hasil analisis data di atas disimpulkan bahwa perangkat pembelajaran IPA Fisika berbasis model pembelajaran pemaknaan pada materi pokok induksi elektromagnet layak, praktis, dan efektif digunakan dalam pembelajaran untuk melatihkan keterampilan proses sains dan menanamkan karakter siswa SMP.